2023
DOI: 10.3390/electronics12041024
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Lung Cancer Image Classification and Segmentation Algorithm Based on an Improved Swin Transformer

Abstract: With the advancement of computer technology, transformer models have been applied to the field of computer vision (CV) after their success in natural language processing (NLP). In today’s rapidly evolving medical field, radiologists continue to face multiple challenges, such as increased workload and increased diagnostic demands. The accuracy of traditional lung cancer detection methods still needs to be improved, especially in realistic diagnostic scenarios. In this study, we evaluated the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This study demonstrates the use of distributed computation, federated learning, and complicated mathematical representations to protect patient privacy, facilitate group decision-making, and manage large-scale medical records. In [4], Ruina Sun et al outlined the authors' method for classifying and segmenting pictures of lung cancer using an enhanced Swin Transformer model. The study found that the Swin Transformer model outperformed other models on tasks like as lung cancer segmentation and classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study demonstrates the use of distributed computation, federated learning, and complicated mathematical representations to protect patient privacy, facilitate group decision-making, and manage large-scale medical records. In [4], Ruina Sun et al outlined the authors' method for classifying and segmenting pictures of lung cancer using an enhanced Swin Transformer model. The study found that the Swin Transformer model outperformed other models on tasks like as lung cancer segmentation and classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen Wei et al presented that HRSTNet [ 29 ] replaces the convolutional layer with a transformer module that creates varied resolution feature mapping information. Ruina Sun et al [ 30 ] introduced an effective image classification segmentation technique based on an enhanced Swin transformer, which was designed specifically for lung cancer classification and segmentation. UNeXt model [ 31 ] was proposed by Vishal M. Patel et al as a deep network architecture.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep convolutional neural networks have achieved great success in image processing [11][12][13] and have also been introduced into the field of medical imaging [14]. There have been many studies applying deep convolutional neural networks to computer-aided detection systems for pulmonary nodules.…”
Section: Lung Nodule Detectionmentioning
confidence: 99%